Internships in psychology : the APAGS workbook for writing successful applications and finding the right fit - Williams-Nickelson, Carol; Prinstein, Mitchell J., 1970-; Keilin, W. Gregory (American Psychological Association, 2019)
This authoritative, hands-on book provides doctoral-level psychology students with all the resources they need to successfully navigate the internship application process. Topics include the most common reasons why people don't secure a position; how many sites to apply to; rank ordering your list of programs; writing essays, cover letters, and your curriculum vitae; securing strong letters of recommendation; preparing for interviews; sending thank you notes; receiving Match results; and more. Since the third edition of this book was released, the online application process and the internship marketplace have undergone significant changes, such as the growing importance of accreditation. This fourth edition provides updated information that will help your applications stand out to your internship programs of choice. Advice is also offered to directors of clinical training so they can guide and support students during this challenging process. This resource is provided to students by the American Psychological Association of Graduate Students---the premier group committed to representing, leading, advocating, and developing resources for graduate psychology students.